2000
DOI: 10.1097/00005344-200011000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Differential Pattern of Endothelin-1-Induced Inotropic Effects in Right Atria and Left Ventricles of the Human Heart

Abstract: In human right atrium, endothelin A (ET(A)) receptors couple to both inositol phosphate formation and inhibition of adenylylcyclase, whereas in human left ventricle, ET(A) receptors couple only to inositol phosphate formation. To find out whether this might be of functional relevance, we studied, in right atria obtained from 32 patients undergoing coronary bypass grafting without apparent heart failure, and in right atria and left ventricles from eight patients with end-stage heart failure (NYHA IV) undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…In mouse ventricular tissue, ET-1 also induced a long-lasting negative inotropic effect, which was, however, attributed to ET A stimulation (24) and seemed to be specific of this animal species (24,47). Some authors attributed the negative inotropic of ET-1 to concomitant ␤-adrenoceptor stimulation (6,11,64), a mechanism that presumably did not contribute to the effects we observed because our experiments were performed in the presence of the ␤-blocking agent atenolol.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In mouse ventricular tissue, ET-1 also induced a long-lasting negative inotropic effect, which was, however, attributed to ET A stimulation (24) and seemed to be specific of this animal species (24,47). Some authors attributed the negative inotropic of ET-1 to concomitant ␤-adrenoceptor stimulation (6,11,64), a mechanism that presumably did not contribute to the effects we observed because our experiments were performed in the presence of the ␤-blocking agent atenolol.…”
Section: Discussionmentioning
confidence: 84%
“…The relative contribution of ET A and ET B receptors to this effect remains, however, unclear. Most of these studies showed an initial transient negative, followed by a sustained positive inotropic effect (7,11,37,46,57,58). This pattern was mainly reported in atrial tissue (11,37,46), being observed in ventricular tissue only with higher concentrations of ET-1 (57,58).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Experiments on isolated LV cardiomyocytes in rabbits [42] and humans [43] and on isolated human LV muscle strips [44][45][46] describe a positive inotropic effect of ET-1 mediated by ET A receptors. These discrepancies may be the result of differences between species in the inotropic effects of ET A receptor stimulation or differences between effects that can be revealed in vivo compared with in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Turklāt vidēji cieša pozitīva korelācija šajā grupā bija arī starp ChgA un beta defensīnu pozitīvo šūnu relatīvo daudzumu. Tādējādi varam spriest, ka pozitīva inotropa reakcija(Dhein et al, 2000). Vēl viens nozīmīgs ET-1 efekts uz miokardu ir pārmērīga kardiomiocītu hipertrofija(Ito et al, 1994).…”
unclassified